Front Cover: Green Hydrothermal Synthesis of Fluorescent 2, 3‐Diarylquinoxalines and Large‐Scale Computational Comparison to Existing Alternatives (ChemSusChem 8/2021). Issue 8 (6th April 2021) - Amaya‐García, Fabián; Caldera, Michael; Koren, Anna; Kubicek, Stefan; Menche, Jörg; Unterlass, Miriam M.
Abstract : The Front Cover shows the synthesis of various quinoxalines in nothing but "hot water". Aromatic quinoxalines can be synthesized in down to 10 min from the starting compounds in stoichiometric ratio in water at 230 °C through microwave‐assisted hydrothermal synthesis. The synthetic approach is tolerant to a broad array of functional groups and can be combined with protecting group strategies. A large‐scale computational comparison of all to date existing syntheses towards the presented quinoxalines shows that the hydrothermal approach is the greenest. More information can be found in the Full Paper by F. A. Amaya‐García et al .